2018
DOI: 10.1016/j.forc.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of fatty acid profiles from textiles associated with decomposing pig remains in a temperate Australian environment

Abstract: A methodology to examine the human post-mortem decomposition process has been developed through the monitoring of chemical changes to decomposition fluids absorbed by clothing. Model surface deposition using clothed pigs were established during summer and winter seasons in a temperate region of Australia. Three clothing materials were investigated: cotton, polyester and cotton-polyester. Lipid decomposition products were extracted from the textiles and the fatty acid composition measured as a function of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This latter finding was consistent with the initial signs of cotton degradation reported to establish 149 to 269 days in situ deposition or burial (4) degradation when buried independently, in their highly amorphous, hydrophilic, and absorbent nature (22). On the other hand, preserved to a degree when in contact with cadaveric fluids as reported with porcine-associated cellulosic grave materials (5,6). Buried viscose spectra behaved similarly to buried cotton losing intensity at 3321 cm -1 , 2900 cm -1 , O-H and C-H stretching cellulose vibrations respectively (Figure 2).…”
Section: Clothing Burial and Decompositionsupporting
confidence: 89%
See 1 more Smart Citation
“…This latter finding was consistent with the initial signs of cotton degradation reported to establish 149 to 269 days in situ deposition or burial (4) degradation when buried independently, in their highly amorphous, hydrophilic, and absorbent nature (22). On the other hand, preserved to a degree when in contact with cadaveric fluids as reported with porcine-associated cellulosic grave materials (5,6). Buried viscose spectra behaved similarly to buried cotton losing intensity at 3321 cm -1 , 2900 cm -1 , O-H and C-H stretching cellulose vibrations respectively (Figure 2).…”
Section: Clothing Burial and Decompositionsupporting
confidence: 89%
“…Establishing the time elapsed for unattended death scenes is crucial for investigators to formulate a timeline of events that facilitates identification of the victim, possible suspects and corroboration of witness statements and alibis. Alongside tracking visual deterioration of the grave-associated textiles, anatomical accumulation and composition of decomposition fluids into cadaver clothing also assists in PMI estimation (5)(6)(7). During the active-bloat and purge stages, the carrion begins to release lipid-, protein-and carbohydrate-rich by-products of the degradation processes (8).…”
Section: Introductionmentioning
confidence: 99%
“…The large larval masses feeding on the donors in the summer may also have contributed to elevated protease activities, as these larvae are known to secrete proteases ( Pinilla et al, 2013 ). Other decomposition studies have reported seasonal differences in decomposition processes, for example, different microbial community compositions ( Breton et al, 2016 ), number and abundance of volatile organic compounds produced ( Forbes et al, 2014 ) and differential transformation of fatty acids in decomposition fluid ( Ueland et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%